Correction: Brázda, V. and Coufal, J. Recognition of Local DNA Structures by p53 Protein. Int. J. Mol. Sci. 2017, 18, 375 - Brázda, Václav; Coufal, Jan (International journal of molecular sciences, 2018)
The authors wish to make the following corrections to their paper [1] [...].